Edible medicinal and non medicinal plants: Volume 3, fruits - Lim, T. K. (Springer Netherlands, 2012)
This book continues as volume 3 of a multi-compendium on Edible Medicinal and Non-Medicinal Plants. It covers edible fruits/seeds used fresh, cooked or processed into other food products, or used as vegetables, spices, stimulants, edible oils  and beverages. It encompasses species from the following families: Ginkgoaceae,  Gnetaceae, Juglandaceae, Lauraceae, Lecythidaceae, Magnoliaceae, Malpighiaceae, Malvaceae, Marantaceae, Meliaceae, Moraceae, Moringaceae, Muntigiaceae, Musaceae, Myristicaceae and Myrtaceae. The edible species dealt with in this work include to a larger extent lesser-known, wild and underutilized crops and also common and widely grown crops. To help in identification of the plant, edible parts and food products more than 400 coloured illustrations are included. As in the preceeding  two volumes, topics covered include: taxonomy (botanical name and synonyms); common English and vernacular names; origin and distribution; agro-ecological requirements; edible plant parts and uses; plant botany; nutritive, medicinal and pharmacological properties with up-to-date research findings; traditional medicinal uses; other  non-edible uses; and selected/cited  references for further reading. This volume has  separate  indices for scientific and common names; and separate scientific and medical glossaries.   As in the preceeding  two volumes, topics covered include: taxonomy (botanical name and synonyms); common English and vernacular names; origin and distribution; agro-ecological requirements; edible plant parts and uses; plant botany; nutritive, medicinal and pharmacological properties with up-to-date research findings; traditional medicinal uses; other  non-edible uses; and selected/cited  references for further reading. This volume has  separate  indices for scientific and common names; and separate scientific and medical glossaries.